The Ethical Philosophy of Eudaimonism by Ibn Sina Based on An-Nakhjuwānī’s Work Syarḥ al-Isyārāt - Akhmad Rofii Damyati; Hatice TOKSÖZ (University of Darussalam Gontor, Indonesia, 2023)
This article examines a branch of philosophy that answers practical questions about human action concerning their values, principles and norms that determine whether an action is appropriate or not, good or not, beneficial or not for oneself, namely ethics. The problem is that in many classical literatures, this branch of ethics always discusses happiness or eudaimonism; that is, the extent to which one’s understanding of happiness, pleasure, and enjoyment is achieved. The question is what is the relationship between happiness and ethics, and why is it an important issue? The research originating from the textual study of two manuscript texts, namely Akmaluddīn an-Nakhjuwānī's work entitled “Syarḥ al-Isyārāt” on Ibn Sīnā's work entitled “Al-Isyārāt wa al-Tanbīhāt,” will address this issue by analyzing the content within the texts. The results of this study reveal that the ethicalphilosophy presented is deeply influenced by Islamic nuances, although the Peripatetic traditionis also strongly present in its perspective. It can be said that the described concept of ethics is highly eschatological. As an implication, an-Nakhjuwānī's ethical philosophy also reveals the spiritual side of Ibn Sīnā, who is generally known as a highly rational philosopher. This research also uncovers that an-Nakhjuwānī's ethical discourse displays more religious terms compared to Ibn Sīnā.